Development of a building automation system using power line communications - Cheah, Peng Huat. (2010)
Power line communication (PLC) is an alternative communications method whereby data signals are transmitted over existing power lines. Over the last decades, the power line technology has received an increasing attention due to its benefits especially in the area of building automation industry and building energy management and monitoring. This final year project revisits the related work in using PLC technology for communication within automotive domain and highlights its advantages and disadvantages. The final goal of the project is to demonstrate the uses of some of the building automation system like auto lighting and ventilation control to save energy in a building. A working model and a Graphical User Interface (GUI) are created to control and display data through local area network within the building for remote control. With the working model, it may serve as a standard for further work in this field.